Evolution of Human Nutrition: A Focus on Food Production and its Impact on Health - Rodríguez León, André (2024)
The text examines the evolution of human nutrition from the emergence of the first hominids to the present day, focusing on how changes in food production have impacted both health and the environment. The objective of the research was to analyze these changes, emphasizing the responsibility of food companies in promoting sustainable and healthy practices. The methodology employed was a literature review, selecting 47 relevant articles published between 2016 and 2024. The findings revealed that although technological advances in food production have improved food security, they have also contributed to the rise in chronic diseases such as obesity and type 2 diabetes. Notably, the negative impact of consuming ultra-processed foods and refined grains was highlighted, along with the influence of marketing on dietary decisions. The study concluded that it is essential to reassess current production methods and food policies, promoting healthier and more sustainable diets to mitigate these negative effects.